Controlled nitridation of tantalum (oxy)nitride nanoparticles towards optimized metal-support interactions with gold nanocatalysts. Issue 108 (20th October 2015) - Yang, Xiaoyun; He, Sina; Shu, Yijin; Shi, Zhangping; Guo, Yulin; Gao, Qingsheng; Tang, Yi
Abstract : Optimized metal-support interactions were achieved on ionothermally prepared tantalum (oxy)nitrides with controlled nitridation, and the as-formed Au δ − species on TaON is efficient for nitrobenzene hydrogenation. Abstract : The electron regulation on supports can vary metal-support interactions with loaded metals in heterogeneous catalysis. In this paper, a facile Sr 2+ -mediated ionothermal route was introduced to control the nitridation degree in tantalum (oxy)nitrides, resulting in varied electronic properties and optimized interactions with gold nanocatalysts. A new mechanism was proposed that the formation of SrTa4 O11 intermediates facilitated the replacement of O by N in controlled nitridation, and more importantly avoided undesired over-nitridation. As expected, the TaON support with defined nitridation promoted electronic metal-support interactions to generate Au δ − species, which was highly active for the thermal hydrogenation of nitrobenzene due to the moderated adsorption and effective activation on Au δ − in Au/TaON. This work elucidated the optimized metal-support interactions achieved on controllably nitridated supports, opening up new opportunities for the development of efficient nanocatalysts.